The future of Portuguese public administration and a new agenda for public administration sciences in the 21st century - Tavares, Luis V.; Alves, Andre A. (2006)
This paper addresses the changing role of the Portuguese state, the present priority assigned to the process of reform and the new challenges to be overcome by public administration. Such processes are demanding a new agenda for education and research in public administration sciences, shifting from the public law paradigm to an interdisciplinary problem-solving approach and giving special attention to 10 key areas of study, which we describe in the final section of the paper. It should be noted here that the opinions expressed in this paper do not necessarily reflect the position of their institutions. - Reproduced.
Keywords: Public administration - Portuguese - 21st century; Public administration